Pre-exposure prophylaxis in a sexual health clinic for Men who Have Sex with Men in Portugal. (13th November 2019) - Ribeiro, S; Rocha, M
Abstract: Background: Pre-exposure prophylaxis (PrEP) is defined as the use of antiretroviral drugs to prevent HIV acquisition in uninfected individuals. Recognizing the increasing use of informal PrEP in Portugal, CheckpointLX, a community clinic targeted for MSM in Lisbon, Portugal, began offering counselling and follow-up services prior to formal introduction. This study aims to characterize PrEP users attending CheckpointLX before formal PrEP introduction in Portugal, and those who were referred to PrEP in the National Health Service (NHS) following formal approval of PrEP. Methods: Data was collected by peer counsellors between May 2015 and September 2018 and inserted in a database. Medical care followed EACS recommendations for PrEP eligibility, initiation and follow up. For formal PrEP, the General-Directorate for Health's PrEP guidelines checklist was used. Results: Until the end of May 2018, CheckpointLX had a total of 90 appointments for Wild PrEP, of which 64 (71%) were first time visits. As for the 380 service users referred to the NHS, most were Portuguese (N = 318, 84%), and the mean age was 31 (8.9) years old. Condomless sex in the last six months with partners of unknown HIV status was the most common eligibility criteria (N = 59, 83%). Conclusions: PrEP delivery should be complemented with effective information on the importance of immunization and education on safer practices of drug administration, in the scope of broader preventive sexual health care. Much remains to be done in Portugal to ensure that PrEP is available to those who need it the most. Offering PrEP at community clinics could be a first step. Key messages: Condomless sex in the last six months with partners of unknown HIV status was the most common eligibility criteria for PrEP. PrEP delivery should be complemented with effective information on the importance of immunization and education on safer practices of drug administration.